AAO-HNSF CORE Grant Acquisition Is Associated with Greater Scholarly Impact. (January 2014) - Eloy, Jean Anderson; Svider, Peter F.; Folbe, Adam J.; Setzen, Michael; Baredes, Soly
Objective: To determine whether receiving funding from the American Academy of Otolaryngology—Head and Neck Surgery Foundation (AAO-HNSF) Centralized Otolaryngology Research Efforts (CORE) grant program is associated with career choice (in terms of practice setting) and scholarly impact. Study Design and Setting: Examination of bibliometrics among academic otolaryngologists, including CORE grants funding history. Methods: An Internet search was conducted to determine the current practice setting and, for academic otolaryngologists, academic rank of individuals receiving CORE grants since 1985. The Scopus database was used to determine scholarly impact, as measured by the h -index, and publication experience (in years) of these practitioners along with a "control" cohort of nonfunded academic otolaryngologists. Results: Of 432 unique individuals receiving CORE grant funding since 1985, 44.4% are currently academicians. This cohort had a higher h -index (mean, 11.9; median, 10; interquartile range [IQR], 6-18) than their non–CORE grant–funded academic peers (mean, 9.2; median, 7; IQR, 3-13; P = .002) and colleagues who are not currently in academic practice (mean, 4.4; median, 3; IQR, 0-6; P < .001). CORE grant–funded academic otolaryngologists had a statistically higher scholarly impact on controlling for academic rank and among practitioners with greater than 10 years of publication experience. No statistical differences in academic promotion patterns were noted between those with and those without a CORE grant funding history. Conclusions: Procurement of an AAO-HNSF CORE grant is associated with greater scholarly impact, as measured by the h -index. This relationship persists among practitioners with more than 10 years of publication experience, as well as upon comparison of CORE grant–funded and non–CORE grant–funded otolaryngologists at all academic ranks. Practitioners awarded these grants may be more likely to go into and remain in academic practice.